2010
DOI: 10.1002/anie.201000485
|View full text |Cite
|
Sign up to set email alerts
|

Selective Knockout of Gold Active Sites

Abstract: It's a knockout! When the surface of gold electrodes is treated with hydroxyl radicals, the electron‐transfer rates ks of electrochemical reactions involving radical intermediates are drastically reduced (see picture). This observation can be explained by the selective knockout of gold active sites associated with partially filled d orbitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…In contrast, metastable states are often of low lattice coordination and as a result are thermodynamically active. Nowicka et al [36] have shown that these sites can be selectively 'knocked out' by treatment with hydroxyl radicals, suggesting that surface defects are the loci of partially filled d-orbitals that can stabilise free-radical intermediates. Similarly, theoretical calculations performed by Sun et al [37] on the adsorption of oxygen on Au surfaces further highlight the role of such defect sites in surface catalysis.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, metastable states are often of low lattice coordination and as a result are thermodynamically active. Nowicka et al [36] have shown that these sites can be selectively 'knocked out' by treatment with hydroxyl radicals, suggesting that surface defects are the loci of partially filled d-orbitals that can stabilise free-radical intermediates. Similarly, theoretical calculations performed by Sun et al [37] on the adsorption of oxygen on Au surfaces further highlight the role of such defect sites in surface catalysis.…”
Section: Introductionmentioning
confidence: 98%
“…1 shows cyclic voltammograms for p-hydroquinone, Ru(NH 3 ) 6 3+ , ferrocenemethanol, and Fe(CN) 6 4-observed in PBS buffer. As the electrochemical behavior of p-hydroquinone highly depends on the electrocatalytic activity of an electrode, 16) p-hydroquinone was selected for the evaluation of the electrocatalytic activity. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A), with eight cantilevers (500 m by 100 m by 1 m) per array, were purchased from Concentris GmbH, Switzerland. They were cleaned under UV light for 1.5 h in order to remove possible impurities and smooth the gold surface (26). This step is crucial for the following functionalization step as an irregular gold surface can lead to a decrease in cantilever sensitivity (27).…”
Section: Methodsmentioning
confidence: 99%